Rethinking and Queering Relationships in the Age of Same-sex Marriage: Multiplicities, Intensities, and New Potentialities - Yulius, Hendri (Jurnal Perempuan, 2018)
This essay presents a theoretical discussion, analysis, and formulation to reconfigure new meanings, potentialities, and multiplicities of homosexual relationship/s. After a brief discussion on the rapid popularisation of marriage equality as the primary goal of queer movements, an overview of queer critique of marriage is provided. Attention given to the notion of homonormativity and the sharp criticism from queer negativity/queer anti-social. For these critiques, subjects are encouraged to occupy the abject position, which I argue, only further depoliticise queer politics. After a critical overview of this political stance, I offer Foucault and Deleuze accounts to explore multiple forms of relationships beyond marital institution, focusing on the ways in which relationships are to be understood as in terms of potentialities, intensities, and emergent forms and functions beyond the existing language capacities and formalised forms. This essay should, however, not situated as masterly or prescriptive, but rather a modest effort to spur more critical concerns,discussions, and debates among queer Indonesians.